2021
DOI: 10.3390/cancers13112538
|View full text |Cite
|
Sign up to set email alerts
|

The Present and Future of Neoadjuvant Endocrine Therapy for Breast Cancer Treatment

Abstract: Endocrine therapy (ET) has established itself as an efficacious treatment for estrogen receptor-positive (ER+) breast cancers, with a reduction in recurrence rates and increased survival rates. The pre-surgical approach with chemotherapy (NCT) has become a common form of management for large, locally advanced, or high-risk tumors. However, a good response to NCT is not usually expected in ER+ tumors. Good results with primary ET, mainly in elderly women, have encouraged studies in other stages of life, and now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 126 publications
0
16
0
Order By: Relevance
“…Specifically, Ki67 ≤ 10% after 2 to 4 weeks of NET has been used in several trials as a marker of response to NET and has been shown to correlate with both radiographic response to NET and with improved breast cancer outcomes. 10,12,15,40 Although the use of Ki67 to guide therapeutic decisions has previously been hampered by lack of analytical validity of the Ki67 assay, the International Ki67 in Breast Cancer Working Group has developed a standardized methodology for scoring Ki67, which was utilized in our study. 28 Selecting patients with HR+ tumors most likely to respond to NET is both challenging and critically important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Ki67 ≤ 10% after 2 to 4 weeks of NET has been used in several trials as a marker of response to NET and has been shown to correlate with both radiographic response to NET and with improved breast cancer outcomes. 10,12,15,40 Although the use of Ki67 to guide therapeutic decisions has previously been hampered by lack of analytical validity of the Ki67 assay, the International Ki67 in Breast Cancer Working Group has developed a standardized methodology for scoring Ki67, which was utilized in our study. 28 Selecting patients with HR+ tumors most likely to respond to NET is both challenging and critically important.…”
Section: Discussionmentioning
confidence: 99%
“…Effective NET induces cell cycle arrest; hence reduction in the percentage of Ki67-positive tumor cells, as measured by immunohistochemistry, is used as a measure of endocrine responsiveness. Specifically, Ki67 ≤10% after 2 to 4 weeks of NET has been used in several trials as a marker of response to NET and has been shown to correlate with both radiographic response to NET and with improved breast cancer outcomes 10,12,15,40. Although the use of Ki67 to guide therapeutic decisions has previously been hampered by lack of analytical validity of the Ki67 assay, the International Ki67 in Breast Cancer Working Group has developed a standardized methodology for scoring Ki67, which was utilized in our study 28…”
Section: Discussionmentioning
confidence: 99%
“…Endocrine therapy refers to drugs to block the promoting effect of sex hormones on breast cancer cells according to the expression of ER and PR in breast cancer tissue [ 30 ]. Anastrozole is a potent, selective aromatase inhibitor of triazole, blocking estrogen biosynthesis by inhibiting aromatase [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The systematic therapy for ER-positive breast cancer includes both chemotherapy and endocrine therapy, which can be given in adjuvant and neoadjuvant settings. Neoadjuvant chemotherapy (NCT), neoadjuvant endocrine therapy (NET), and neoadjuvant sequential endocrine-chemotherapy (NECT) have been used in ER-positive breast cancer for almost two decades mostly to downstage tumors before breast-conserving surgery (BCS) [ 2 ]. Compared with NCT, NET has less cytotoxicity and is currently applied in older patients and patients with ER-rich tumors which are defined with an “Allred score” greater than 5 [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%